2018
DOI: 10.3389/fonc.2018.00378
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality Among Ethnic German Migrants From the Former Soviet Union

Abstract: Germany is a country known for immigration. In 2015, 21% of the general population in Germany consisted of individuals with a migration background. This article focuses on cancer-specific incidence and mortality among one of the biggest migrant groups in Germany: the resettlers. Resettlers are ethnic Germans who mainly immigrated from the Russian federation and other countries of the former Soviet Union after its collapse in 1989. We investigated differences between resettlers and the general German population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 29 publications
(36 reference statements)
3
24
0
Order By: Relevance
“…One of these 7 studies did not report a statistically significant increased SMR in the FSU immigrant population to Germany, 25 but the other 6 did report statistically significant increases when migrating to Germany, Canada, and Israel; sex-specific rates varied from 1.44 to 1.91 among males, 1.40 to 2.56 among females, and 1.40 to 2.56 for combined sexes ( Table 2). [26][27][28][29][30][31] Two studies reported increased SMR for first-generation Japanese immigrants to Brazil. One study reported ranges of 61-88 and 49-72 for men and women from 1980 to 2000, respectively (Japanese mortality in Japan used as a reference, with the rates listed found to be statistically significant when compared with the Brazilian born population).…”
Section: Gastric Cancer-related Mortality Among Immigrants From High-mentioning
confidence: 99%
“…One of these 7 studies did not report a statistically significant increased SMR in the FSU immigrant population to Germany, 25 but the other 6 did report statistically significant increases when migrating to Germany, Canada, and Israel; sex-specific rates varied from 1.44 to 1.91 among males, 1.40 to 2.56 among females, and 1.40 to 2.56 for combined sexes ( Table 2). [26][27][28][29][30][31] Two studies reported increased SMR for first-generation Japanese immigrants to Brazil. One study reported ranges of 61-88 and 49-72 for men and women from 1980 to 2000, respectively (Japanese mortality in Japan used as a reference, with the rates listed found to be statistically significant when compared with the Brazilian born population).…”
Section: Gastric Cancer-related Mortality Among Immigrants From High-mentioning
confidence: 99%
“…The AMIN study (Aussiedler in Münster -Incidence Cohort Study, N = 32,972 [19]) is a retrospective, register-based cohort study that provides information on breast cancer incidence among resettlers from the FSU and the general German population. The study was conducted in the administrative district (AD) of Münster in cooperation with the federal cancer registry of NRW.…”
Section: Study Populationsmentioning
confidence: 99%
“…However, sensitivity analyses showed negligible differences in the results. A detailed discussion of the strengths and weaknesses of the AMIN study has been published elsewhere [19].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mortality ratios showed site-specific cancer differences [7]. Focusing on cancer incidence in comparison to the respective regional populations in Germany, female resettlers had lowered overall, colorectal, lung and breast cancer incidence, while male resettlers showed lowered overall and prostate cancer incidence, but elevated stomach cancer incidence [8, 9]. Furthermore, overall cancer incidence converged since 1994 reaching levels of the general German population in 2013 [8].…”
Section: Introductionmentioning
confidence: 99%